Sickle Cell Disease: Management options and challenges in developing countries - Daniel Ansong; Alex Osei-Akoto; Delaena Ocloo; Kwaku Ohene-Frempong Ohene-Frempong (Mediterranean Journal of Hematology and Infectious Diseases)
Sickle Cell Disease (SCD) is the most common genetic disorder of haemoglobin in sub-Saharan Africa. This commentary focuses on the management options available and the challenges that health care professionals in developing countries face in caring for patients with SCD.